Peran Peran Akademisi dalam Peningkatan Kualitas SDM melalui Penggunaan Platform Teknologi Digital - Sutarmin Sutarmin (Institute for Research and Community Services, 2023)
The Ministry of Education, Culture, Higher Education and Research & Technology is an organization that is self-aware and must always change. This awareness is manifested in the form of involving academics to catch up to improve the quality of human resources (HR). One of the activities involving academics to improve school human resources is using digital technology platforms in driving schools or in short it is called digitization in schools. Activities are carried out online using Google Meet media on September 12, 2022, for 8 JP (class hours) with 1 JP = 45 minutes. Participants were school principals, supervisors and learning committees from SMAN 1 Kejobong and SMAN 1 Bobotsari Purbalingga. SMAN 1 Dukuhwaru, SMAN 1 Slawi and SMAN 2 Slawi Tegal Regency Bimtek begins with introductions, ice-breaking, and learning through the stages M-E-R-R-D-E-K-A (Starting from the participants themselves, Exploration of concepts, Space for Collaboration, Guided Reflection, Contextual Demonstrations, Elaboration of Understanding and Real Action). This activity has an impact on increasing the understanding and competence of school principals, supervisors and teachers who are members of the learning committee of each education unit. The participants were very enthusiastic because this was a breakthrough in managing administration and learning which was supported by technology and digital platforms.